Density functional investigations of the Rh-catalyzed hydroformylation of 1,3-butadiene with bisphosphite ligands - Schmidt, Sebastian; Deglmann, Peter; Hofmann, Peter (ACS catalysis, 2014)
The catalytic cycle of the Rh-catalyzed monohydroformylation of 1,3-butadiene with a triptycene-derived bisphosphite ligand was investigated with density functional theory, as it determines the selectivity of the 1,4-bis-hydroformylation of 1,3-butadiene to adipic aldehyde, a dream reaction of chemical industry. Out of the variety of possible reactive pathways, two dominant ones were highlighted leading to the monoaldehydes 3-pentenal and 4-pentenal, which experimentally also are the main primary products. With catalysts like the one studied here, which are highly n-selective and reactive for 1-alkene hydroformylation, 4-pentenal is known to be exclusively converted to the bis-hydroformylation product adipic aldehyde. An η3-crotyl complex formed by iso-insertion of an (η2-butadiene)Rh(H) species, not involved in hydroformylation reactions of 1-alkenes and requiring a slightly smaller activation barrier than the desired n-insertion, could be identified as an important intermediate for the monohydroformylation of butadiene. Once formed, this η3-crotyl species opens up an unproductive exit channel within the catalytic reaction mechanism, which does not lead to adipic aldehyde. Free energy profiles in solution were calculated in order to find the intermediates and transition states that govern turnover frequency (TOF) and selectivity: The Rh crotyl complex and the reductive elimination transition state most likely limit the TOF, while the prediction of the regioselectivity is more complicated and depends on several steps.
Gesehen am 15.07.2020